2006
DOI: 10.1021/ol0626387
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel C2-Symmetric Chiral Piperazines and an Application to Asymmetric Acylation of σ-Symmetric 1,2-Diols

Abstract: [Structure: see text] A novel alicyclic chiral C2-symmetric piperazine, (S,S)-7, is designed and synthesized from L-proline. Benzoylation of a series of cyclic and acyclic meso-1,2-diols with a catalytic amount of (S,S)-7 and CuCl2 provided optically active monobenzoates with high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…CycloA C H T U N G T R E N N U N G (Pro,Pro) (11) was prepared from the commercial HCl salt of l-proline in the presence of NaHCO 3 in 50% yield. [18] As expected, we found that cycloA C H T U N G T R E N N U N G (Pro,Pro) (11) when in contact with triplet oxygen in DMF did not give rise to the corresponding peroxide 12 (Table 1). The peroxidation of such deriv- …”
Section: Resultssupporting
confidence: 78%
“…CycloA C H T U N G T R E N N U N G (Pro,Pro) (11) was prepared from the commercial HCl salt of l-proline in the presence of NaHCO 3 in 50% yield. [18] As expected, we found that cycloA C H T U N G T R E N N U N G (Pro,Pro) (11) when in contact with triplet oxygen in DMF did not give rise to the corresponding peroxide 12 (Table 1). The peroxidation of such deriv- …”
Section: Resultssupporting
confidence: 78%
“…A new C 2 -symmetric quaternary ammonium salt 2 was conveniently prepared by simple dialkylation of a known diamine 1, which was synthesized from L-proline according to literature procedure [24] (Scheme 1). To investigate the feasibility of this C 2 -symmetric quaternary ammonium salt applying to phase-transfer catalysis, we carried out Michael addition reactions of various active methylene compounds to aromatic a, b-unsaturated ketones under PTC conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplying Eqns (7), (8), (9), (10), and (11) by a factor of 10 and Eqns (12), (13), (14), and (15) by a factor of five and Eqn (16) by a factor of two, and then summing them with each other results in the overall reaction with the stiochiometry satisfied. In agreement with the above scheme, assuming a steady state approximation for X þ 1 , the rate equation obtained for the uncatalysed process is…”
Section: Hmno 4 ð7þmentioning
confidence: 99%